2020
DOI: 10.1530/ec-19-0555
|View full text |Cite
|
Sign up to set email alerts
|

Does glucocorticoid exposure explain the association between metabolic dysfunction and tendinopathy?

Abstract: Background While metabolic health is acknowledged to affect connective tissue structure and function, the mechanisms are unclear. Glucocorticoids are present in almost every cell type throughout the body and control key physiological processes such as energy homeostasis, stress response, inflammatory and immune processes, and cardiovascular function. Glucocorticoid excess manifests as visceral adiposity, dyslipidemia, insulin resistance, and type 2 diabetes. As these metabolic states are also associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…For example, as the effector molecules of the stress response, GCs are known to increase the consumption of foods enriched in fat and sugar, but acute stress usually results in decreased eating whereas chronic stress results in increased eating [41]. GCs are known as catabolic molecules, but glucocorticoid excess manifests as visceral adiposity [42]. P. vulgaris treatment in current research showed a decreased appetite but an increased ratio of body weight gain to food intake.…”
Section: Discussionmentioning
confidence: 58%
“…For example, as the effector molecules of the stress response, GCs are known to increase the consumption of foods enriched in fat and sugar, but acute stress usually results in decreased eating whereas chronic stress results in increased eating [41]. GCs are known as catabolic molecules, but glucocorticoid excess manifests as visceral adiposity [42]. P. vulgaris treatment in current research showed a decreased appetite but an increased ratio of body weight gain to food intake.…”
Section: Discussionmentioning
confidence: 58%
“…48 GCs are known as catabolic molecules, but GC excess manifests as visceral adiposity. 49 Similarly, P. vulgaris treatment shows a decreased appetite, but an increased ratio of body weight gain to food intake. Likewise, an elevated plasma BDNF level and hypothalamic BDNF expression, coupled with a down-regulated hepatic BDNF expression occurred in the current research.…”
Section: Discussionmentioning
confidence: 98%
“…27 BMI was calculated as kg/m 2 , and the subjects were classified as running vs. no running (<0 h/week) smokers vs. non-smokers based on self-reporting. Likewise, regular use of painkillers, the treatment with lipid-lowering statins, 28 and medication as treatment for asthma/bronchitis, 29 which may cause tendon damage, were registered based on self-reporting.…”
Section: Assessmentsmentioning
confidence: 99%